2003
DOI: 10.1001/archsurg.138.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Gastrojejunostomy During Laparoscopic Gastric Bypass

Abstract: Hypothesis: Although perceived as a more technically demanding and time-consuming technique, the handsewn gastrojejunostomy during laparoscopic Rouxen-Y gastric bypass (RYGB) is associated with fewer complications and lower costs than stapled techniques.Design: A retrospective medical record review of prospectively collected data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(105 citation statements)
references
References 16 publications
5
95
1
4
Order By: Relevance
“…Noshiro et al [11] reported their new technique of making a gastrojejunostomy on the stomach transecting line for a very small remnant stomach, which needed time for suturing the extra incision after gastrojejunostomy. In the present study, we tried to find an easier and faster method for gastrojejunostomy, and we felt that a procedure using a circular-stapling device might be suitable [20,21]. We applied a modified technique using the OrVil TM system and a 25 mm circular stapler.…”
Section: Discussionmentioning
confidence: 99%
“…Noshiro et al [11] reported their new technique of making a gastrojejunostomy on the stomach transecting line for a very small remnant stomach, which needed time for suturing the extra incision after gastrojejunostomy. In the present study, we tried to find an easier and faster method for gastrojejunostomy, and we felt that a procedure using a circular-stapling device might be suitable [20,21]. We applied a modified technique using the OrVil TM system and a 25 mm circular stapler.…”
Section: Discussionmentioning
confidence: 99%
“…The third accepted technique is the hand-sewn gastrojejunostomy originally promoted by Higa et al [24]. Although hand-sewn anastomoses may take longer to perform, they result in a lower hospital cost, less anastomotic bleeding, fewer stricture complications, and a lower incidence of wound infection [24][25][26]. In addition, the use of absorbable suture to create the gastrojejunostomy reduces the risk of gastrogastric fistula and marginal ulceration [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of marginal ulcer was similar. Similarly, others have found no difference in MU rate with type of anastomosis, including hand sewn vs. circular stapled [20] and linear vs. circular [21,22]. Suggs et al [23] found fewer ulcers with the 21-mm vs 25-mm circular stapler, however.…”
Section: Discussionmentioning
confidence: 94%